Analisis Nilai Keindahan Wisata Bahari di Pantai Tlangoh Bangkalan Menggunakan Metode Scenic Beauty Estimation (SBE): Analysis of the Beauty Value of Marine Tourism at Tlangoh Beach, Bangkalan Using the Scenic Beauty Estimation (SBE) Method - Adhia Reggita Chinta Priwati; Firman Farid Muhsoni (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
The potential for sightseeing in madura is one of the potential for enjoying its natural beauty. The tlangoh village beach Tours are in demand. The purpose of this study is to know the value of beauty on the tlangoh coast. The method of measuring beauty value with scenic beauty colonation (sbe), it is used to assess and analyze the quality of landscapes using the documentaries (location photos) with the presentation of the location (gili labak island). Studies show that 15 landscape photos compared to 4 positive ones and 11 negative ones. Shows there are 4 landscape locations on tlangoh beach better than comparison sites, and 11 landscaping better location Settings. The average score sbe -1.97, suggests that a control site is still better than the tlangoh coast. The lowest score is 82.34 on the 4th landscape photo and 2.11 on the 15th landscape photo. Locations with low value are mostly in natural conditions such as coral reefs, beaches, while the tlangoh beach tourist facilities fare better than comparison points. Improved environmental quality needs to be made to increase the value of beauty at tlangoh beach.